The role of traders in market waste management to promote sustainable environmental development - Shifa Damayanti (Waste Handling and Environmental Monitoring, 2026)
Background: Human activities inevitably generate waste, and in Indonesia, the wholesale and retail trade sector that is employing 17.5% of the working population plays a major role in this process. Traditional markets, as key economic hubs, are significant waste contributors, with national data showing that households and markets produce 14.47% of Indonesia’s total waste. This study examines the role of traders in waste management, where inadequate practices often lead to waste accumulation and unsanitary conditions. Methods: Using a qualitative case study approach, data were gathered through field observations and interviews with traders, managers, and cleaning staff. Findings: The study found that hold substantial day-to-day control over how waste is generated and sorted, yet most exercised this power inconsistently and individually, leaving their potential as central stakeholders largely untapped. Although market managers and cleaning staff held the formal legitimacy and authority to set procedures and supply facilities, limited budgets, irregular education, and weak enforcement constrained their capacity to alter vendor behavior. A persistent intention–behavior gap emerged across informants—many recognized the value of sorting but did not practice it—indicating that waste management at the market operates as much as a social process shaped by supervision, incentives, and peer norms as a technical one. Conclusion: These findings highlight an intention about behavior gap driven by limited facilities, weak supervision, and minimal incentives. The study concludes that improving trader participation through continuous education, better infrastructure, and collaborative programs is essential for achieving sustainable market waste management. Novelty/Originality of this article: This study provides novel insights into the intention–behavior gap in traders’ waste management practices in traditional markets, highlighting the influence of limited facilities, weak supervision, and minimal incentives on participation in sustainable waste management.